2014
DOI: 10.1007/s10753-014-9850-0
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Expression Is Increased in Leukocytes in Experimental Acute Pancreatitis

Abstract: Severe acute pancreatitis (AP) induces a systemic inflammatory disease that is responsible for high mortality rates, particularly when it is complicated by infection. Therefore, differentiating sepsis from the systemic inflammation caused by AP is a serious clinical challenge. Considering the high metabolic rates of leukocytes in response to stress induced by infection, we hypothesized that the transcription coactivator peroxisome proliferator-activated receptor gamma coactivator 1 (PGC-1α), a master regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Sodium taurocholate caused severe histologic damage similar to that observed for other experimental models 14 16 . Significant edema, intense infiltration of leukocytes and intra-pancreatic bleeding shows the similarity of the histopathology of experimental lesions with moderate-to-severe pancreatitis in humans 14 , 15 . Mortality in the control group at 24 h was 22%, similar to the mortality (20%) obtained using glycodeoxycholic acid (5–10 mmol) by other research teams.…”
Section: Discussionsupporting
confidence: 80%
“…Sodium taurocholate caused severe histologic damage similar to that observed for other experimental models 14 16 . Significant edema, intense infiltration of leukocytes and intra-pancreatic bleeding shows the similarity of the histopathology of experimental lesions with moderate-to-severe pancreatitis in humans 14 , 15 . Mortality in the control group at 24 h was 22%, similar to the mortality (20%) obtained using glycodeoxycholic acid (5–10 mmol) by other research teams.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, exercise-induced ROS-dependent pathways such as PGC-1alpha are linked with increased mitochondrial biogenesis, antioxidant expression, and inhibition of inflammatory pathways in macrophages [ 73 , 74 , 75 ]. Llimona et al showed that PGC-1alpha expression is crucial for phagocytic stimulus in acute pancreatitis [ 76 ].…”
Section: Redox Homeostasis and Exercise In Macrophagesmentioning
confidence: 99%
“…[2][3][4][5][6] Acute pancreatitis (AP) is an inammatory disorder of the pancreas encountered in emergency settings with an annual incidence range of 13-45/100 000 inhabitants. [7][8][9] Approximately 20% of AP patients develop necrotizing pancreatitis with a high mortality risk, mostly attributed to sepsis and infection of pancreatic and peripancreatic necrotic tissue induced by gutderived bacteria overgrowth and subsequent bacterial translocation. 10 Recently, it has been established that disruption of gut microora is signicantly correlated with "second hit summit" involved in the progression of AP, which demonstrated that gut microbiota is a promising modulator of inammatory cascade in AP pathophysiology.…”
Section: Introductionmentioning
confidence: 99%